2004
DOI: 10.1002/ajhb.20007
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of joint distribution in hand osteoarthritis: Contribution of age, sex, and handedness

Abstract: The most frequent site of osteoarthritis (OA) is the hands, but the pattern of hand OA development remains controversial. Understanding these patterns may assist in evaluating biological aging, determining etiology, and proposing ways of preventing hand OA. We investigated the pattern distribution of OA in hands and the influences of age, sex, and handedness on its development. The study population was comprised of Chuvashians (660 males age 18-89 years and 585 females age 18-90 years). OA development was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 15 publications
3
40
0
5
Order By: Relevance
“…37 However, other investigators failed to reveal any prevalence of OA in the dominant hand. 14,15,38,39 For the DIP joint in particular, patients with unilateral DIP joint OA did demonstrate a preference for their dominant hand. 13 The anatomy and structure of a joint has an intimate relationship with the mechanical stresses and kinematics that affect it.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…37 However, other investigators failed to reveal any prevalence of OA in the dominant hand. 14,15,38,39 For the DIP joint in particular, patients with unilateral DIP joint OA did demonstrate a preference for their dominant hand. 13 The anatomy and structure of a joint has an intimate relationship with the mechanical stresses and kinematics that affect it.…”
mentioning
confidence: 96%
“…However, gender differences were significant only in the DIP joints among individuals aged 50 to 65. 15,19,21,34 Ethnicity is a contributing intrinsic factor of DIP joint OA, as differences in the occurrence and severity of DIP joint OA vary among different populations. For example, prevalence of DIP joint OA is much lower in Chinese subjects than in white subjects.…”
mentioning
confidence: 99%
“…First, OA changes appears before age 30 [25]; and after age 65, 89.29% of males and 97.6% of females in Chuvashian population had at least one aVected joint [20]. In a sub-sample used in this study, 52.04% of study participants had a least one joint with OA (K-L¸2).…”
Section: Discussionmentioning
confidence: 97%
“…Results from previous studies are, however, conflicting [28,29]. Two recent studies showed some preference for osteoarthritis in the DIP or proximal interphalangeal (PIP) joints of the dominant or right hand [9 ,30] while another did not [31].…”
Section: Risk Factors For Hand Osteoarthritis Developmentmentioning
confidence: 95%